Counterfactuals as Strict Conditionals - Iacona, Andrea (2016)
This paper defends the thesis that counterfactuals are strict conditionals. Its purpose is to show that there is a coherent view according to which counterfactuals are strict conditionals whose antecedent is stated elliptically. Section 1 introduces the view. Section 2 outlines a reply to the main argument against the thesis that counterfactuals are strict conditionals. Section 3 compares the view with a proposal due to Åqvist, which may be regarded as its direct predecessor. Section 4 explains how the view differs from contextualist strict conditional accounts of counterfactuals. Finally, section 5 addresses the thorny issue of disjunctive antecedents.